Study of outcome of pregnancy in women with heart disease - Gehlot, Hanslata; Singh, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Heart disease complicates 1% of all pregnancies. Objective of the study is to evaluate the maternal and fetal outcome in patients with cardiac disease in pregnancy. Methods: An observational study was carried out in 25 pregnant women with known or newly diagnosed heart disease at tertiary care hospital. Results: The average age of women was 21-25 (36%), in which primigravida 52% and 48% were multigravida. 56% patients were unbooked and 44% booked. Rheumatic heart disease was the commonest aetiology and was found in 56% of patients. While 16% patients had RHD with PAH. Three (12%) patient had prosthetic valve replacement. 8% patient had Congenital heart disease while 8% had peripartum cardiomyopathy. 60% delivered vaginally and 40% of them had delivered by LSCS for various obstetrical indications. In our study none of the patient required therapeutic termination of pregnancy. Majority of patients 92% in our study group had no obstetric maternal complications. Two (8%) maternal mortality occurred in our study. Low birth weight babies were 24%, preterm labour in 4% patient. 8% babies were growth restricted. Regarding fetal outcome 25 were live birth babies. None of the patient had congenitally malformed baby and there was no perinatal loss in this study. Conclusions: Early diagnosis of heart disease, regular antenatal checkups, institutional delivery and collaboration between cardiologist and obstetrician should result in a fall in maternal deaths from conditions already diagnosed before pregnancy.